Explaining the large disparities in health in the Philippines - Picazo, Oscar F. (2013)
This Policy Note explains the large disparities in health status between the poor and the nonpoor in the Philippines. Key factors include: (1) the persistently large social inequity and chronic poverty; (2) severe underinvestment of the government in health facilities, services, and manpower since the 1970s despite the ballooning population; (3) political instability due to the insurgency problem which has further reduced access to care among households in areas of civil unrest; (4) the character of jobless growth of Philippine development; (5) the archipelagic nature of the country which impinges adversely on the delivery of health resources and households` access to health care; and (6) the frequent disasters in the country and environmental risks, heightened by climate change, which further contribute to health inequity. These challenges are aggravated by long-term perceptible changes in the country`s demography and epidemiology, which often escape officials` focus on the short-term, immediate, and emergency concerns of governing and management. Inefficiency and governance problems exacerbate the situation.
Keywords: Medical care; Health insurance